Minimum Inhibitory Concentration (MIC) Of Liquid Smoke Produced from Piper Betle L Against Salmonella sp and Staphylococcus aureus - Dodi Irwandi; Ai Emalia Sukmawati (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2020)
The betel (Piper betle L) is an herb that has one of the properties, namely as an antibacterial. Several studies have shown green betel leaf extract can inhibit the growth of Gram-positive and Gram negative bacteria. In this study, the antibacterial activity of liquid smoke produced from betel leaf by pyrolysis using a simple pyrolysis reactor was tested. Tests are carried out on 2 types of liquid smoke namely grade 3 which is the first product of the pyrolysis process and grade 2 which is the result of distillation from grade 3. Both types of liquid smoke are prepared into concentration of 100%, 75%, 50%, 25% respectively water as a solvent. Two types of bacteria are used, namely Salmonella sp as Gram-negative bacteria and Staphylococcus aureus as Gram-positive. The test results show that grade 3 and grade 2 liquid smoke give minimum inhibitory concentration (MIC) at the same concentration of 50% against Salmonella sp and, Staphylococcus aureus at 25%, 75% concentrations, respectively.